2017
DOI: 10.1111/1758-2229.12543
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nitrous oxide reductase genes by NasT‐mediated transcription antitermination in Bradyrhizobium diazoefficiens

Abstract: In Bradyrhizobium diazoefficiens, maximal expression of the nitrous oxide reductase gene (nosZ) requires oxygen limitation and the presence of a nitrogen oxide. The putative transcription antiterminator NasT is a positive regulator of nosZ; but in the absence of nitrate, NasT is counteracted by the nitrate sensor NasS. Here, we examined the NasT-mediated mechanism of nosRZDFYLX gene cluster expression. We mapped two transcription start sites of nosR and identified two potential hairpins, H1 and H2, within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…In this work, we have identified two nosR TSS, i.e., TSS 1 and TSS 2 , positioned at +40.5 and +67.5 bp, respectively, from the axis of symmetry of the FixK-like binding site (TTGATCCAGCGCAA). Similarly, a TSS at +40.5 from the axis of symmetry of the FixK box has been recently identified by Sánchez et al (2017) . In contrast to our results, the TSS at +67.5 bp was not identified in the latter studies.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In this work, we have identified two nosR TSS, i.e., TSS 1 and TSS 2 , positioned at +40.5 and +67.5 bp, respectively, from the axis of symmetry of the FixK-like binding site (TTGATCCAGCGCAA). Similarly, a TSS at +40.5 from the axis of symmetry of the FixK box has been recently identified by Sánchez et al (2017) . In contrast to our results, the TSS at +67.5 bp was not identified in the latter studies.…”
Section: Discussionmentioning
confidence: 93%
“…The capacity of B. diazoefficiens to couple N 2 O reduction to growth as well as a role for the NasST regulatory system on modulation of nosZ gene transcription has also been reported ( Sánchez et al, 2013 , 2014 ). Furthermore, recent studies have demonstrated the capacity of NasT to interact with B. diazoefficiens nosR 5′-leader RNA ( Sánchez et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nos ++ mutants retained higher nos expression and N 2 OR activity in both free-living and symbiotic cells than the wild-type nos + strains (Itakura et al, 2013; Sánchez et al, 2014). Comparative analysis of the nos ++ mutant genomes revealed the mechanism underlying the nos ++ phenotype, a point mutation in nasS gene encoding the NO 3 – sensor of the two-component NasST regulatory system (Sánchez et al, 2014, 2017), which will be discussed later.…”
Section: Nitrous Oxide Reductase: the Key Enzyme To Reduce N2o Emissionmentioning
confidence: 99%